1994
DOI: 10.1177/0272431694014004004
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Sociocultural Factors to Eating Attitudes and Behaviors among Middle School Girls

Abstract: Three hundred and eighty-five girls ages 10 through 14 years were surveyed about eating behavior, body satisfaction, concern with being slender, and cues from parents, peers, and magazines in regard to weight management techniques and the importance of slenderness. A majority reported receiving a clear message from fashion magazines and peers or family members that slenderness is important and attainable through dieting and other methods. Two strong correlates of drive for thinness and disturbed patterns of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
220
1
14

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 325 publications
(253 citation statements)
references
References 25 publications
18
220
1
14
Order By: Relevance
“…More recently, media have tremendous effects on people's live. Several studies have shown that girls and women who have higher levels of exposure to media imagery tend to be less satisfied with the way that they look than those with lower levels of exposure [12,[31][32][33] . Botta [34] found that magazine exposure (mediated by social comparison processes) was linked to body dissatisfaction in boys as well as girls and in 2003 argued that: magazine reading, social comparisons and critical body image processing are important predictors of body image and eating disturbances in adolescent boys and girls [35] .…”
Section: Resultsmentioning
confidence: 99%
“…More recently, media have tremendous effects on people's live. Several studies have shown that girls and women who have higher levels of exposure to media imagery tend to be less satisfied with the way that they look than those with lower levels of exposure [12,[31][32][33] . Botta [34] found that magazine exposure (mediated by social comparison processes) was linked to body dissatisfaction in boys as well as girls and in 2003 argued that: magazine reading, social comparisons and critical body image processing are important predictors of body image and eating disturbances in adolescent boys and girls [35] .…”
Section: Resultsmentioning
confidence: 99%
“…In a study of 385 young adolescent girls (ages 10 -14), being teased or criticized about one's weight=shape by family members was significantly correlated with body dissatisfaction, investment in thinness, weight management behavior and eating disturbance. 28 Stormer and Thompson 13 studied 162 female college students and found that a history of being teased about appearance contributed to explaining the variance in body dissatisfaction and eating disturbance, albeit the contribution was small after controlling for factors such as self-esteem, level of obesity, and internalization of sociocultural norms regarding beauty and thinness. In a study of a clinical sample of 115 adult women with binge eating disorders, a history of general appearance teasing was associated with current weight concerns and body dissatisfaction and both general appearance teasing and weight-specific teasing was associated with current psychological functioning.…”
Section: International Journal Of Obesitymentioning
confidence: 99%
“…[9][10][11] Retrospective and cross-sectional studies have found a strong positive association between being teased about weight and disordered eating behaviors, including purging, binge eating, and fasting behaviors. 1,2,[12][13][14] Crosssectional data from Project EAT found that, compared with youths who did not report frequent weight teasing, those who experienced frequent weight teasing had 2.0 times the odds of engaging in unhealthy weight-control behaviors and binge eating. 1 This association was similar for both male and female adolescents.…”
mentioning
confidence: 99%